Application of DE-RF and Fuzzy Model in Camber Control of Hot Rolled Strip - WEI Zhipeng; CUI Guimei; PI Lixiang; LI Tianhao (Journal of Harbin University of Science and Technology, 2023)
In order to solve the problem of slab bending affecting strip quality in 2250mm hot strip rolling process, a method based on data fusion and expert experience is proposed to apply to slab bending control system.Firstly, the differential evolution algorithm is established to optimize the stochastic forest regression model to solve the problem of insufficient accuracy of slab detection lag prediction.The model can effectively predict the bending value of the slab at the exit of the third pass roughing mill, and the estimated error is 96.3% of the slab within the allowable range.Then a fuzzy model is established according to the expert experience and data to solve the manual operation uncertainty problem.The model gets the roll slit tilt value twice respectively, and the experimental results show that the calculated value of the fuzzy model has a small error compared to the actual value and it can provide the roll gap tilt value reliably.Finally, the two roll gap tilt values are added together as the second roll gap tilt value. The simulation results show that the method can effectively reduce the bending of slab, which has practical guiding significance.